Inhibition Effect of Miconazole Nitrate on the Corrosion of Mild Steel in Hydrochloric Acid Medium - J. Ishwara Bhat; Vijaya D. P. Alva (International Journal of Electrochemistry, 2011)
The corrosion inhibition of mild steel by miconazole nitrate, an antifungal drug has been investigated using potentiodynamic polarization, electrochemical impedance spectroscopy technique, and weight loss methods. The experimental results suggested miconazole nitrate is a good corrosion inhibitor for mild steel in 1 M hydrochloric acid medium. The inhibition efficiency increased with increase in inhibitor concentration. The thermodynamic parameters were determined and discussed. The inhibition was assumed to occur via adsorption of the inhibitor molecule on the surface of mild steel following Langmuir adsorption isotherm.